Problematic Smartphone Use—Comparison of Students With and Without Problematic Smartphone Use in Light of Personality - Eichenberg, Christiane; Schott, Markus; Schroiff, Athina (Frontiers in Psychiatry, 2021)
Background: As a device with multiple functions, a smartphone become more and more relevant in everyday life. However, this goes along with an increase in reports about smartphone addiction and its unwanted consequences. One of the most important variables in the etiopathogenesis of addictive smartphone use is personality. Objective: This study aimed to investigate predictors of problematic smartphone use. Clinically relevant differences in personality, psychopathology, and social support between students with and without problematic smartphone use were investigated. Method: All currently enrolled students at the Sigmund Freud University in Vienna (N = 1,836) were surveyed. Response rate was 27.07% (N = 497, age: M = 19.6, SD = 8.04). The Smartphone Addiction Scale (SPAS), the 10-Item Big Five Inventory (BFI-10), the Brief Symptom Inventory (BSI-18), and a questionnaire on social support (F-SozU-K-14) were used. Results: A total of 75 students (15.1% of the total sample) showed problematic smartphone use. In terms of personality, respondents with problematic smartphone use showed significantly higher values for extraversion and neuroticism compared than non-addicted users. Students with problematic smartphone use showed significantly higher levels in terms of depression and anxiety. Contrary to expectations, individuals with problematic smartphone use showed significantly higher values for perceived social support than with individuals without problematic smartphone use. Discussion: Therapy for problematic smartphone use should be carried out taking into account discussed, important etiological factors, such as personality.